The UV surface habitability of Proxima b: first experiments revealing probable life survival to stellar flares - Abrevaya, Ximena Celeste (2020)
We use a new interdisciplinary approach to study the UV surface habitability of Proxima b under quiescent and flaring stellar conditions. We assumed planetary atmospheric compositions based on CO2 and N2 and surface pressures from 100 to 5000 mbar. Our results show that the combination of these atmospheric compositions and pressures provide enough shielding from the most damaging UV wavelengths, expanding the 'UV-protective' planetary atmospheric compositions beyond ozone. Additionally, we show that the UV radiation reaching the surface of Proxima b during quiescent conditions would be negligible from the biological point of view, even without an atmosphere. Given that high UV fluxes could challenge the existence of life, then, we experimentally tested the effect that flares would have on microorganisms in a 'worst case scenario' (no UV-shielding). Our results show the impact that a typical flare and a superflare would have on life: when microorganisms receive very high fluences of UVC, such as those expected to reach the surface of Proxima b after a typical flare or a superflare, a fraction of the population is able to survive. Our study suggests that life could cope with highly UV irradiated environments in exoplanets under conditions that cannot be found on Earth.